Peregrinaciones al santuario del arte moderno. Obras, artistas e intelectuales de América Latina en el taller de Auguste Rodin - María Isabel Baldasarre (Centre de Recherches sur les Mondes Américains, 2017)
At the beginning of the twentieth century, many Latin-Americans traveled to Paris. Settled there or in transit, they sought an education and an artistic life difficult to achieve in their countries of origin. Individual or collective visits to "lighthouse artists" constituted an important part of their sociability and bohemia. The sculptor Auguste Rodin was among the best incarnations of the ideals of the modern "genius". After his big exhibition of 1900, a commercial success and its launching in the international arena, its workshop in Meudon and its Parisian residence became must-sees for every intellectual or artist in Paris. This article analyzes the traces that the workshop and the figure of the sculptor left in the Latin American artists and intellectuals who knew him in Paris. His figure had big relevance for a generation of artists responsible for the introduction of modernism in their native countries. The exchanges, product of these encounters, and the texts of those who expressed their passionate impressions about him are examples of an early moment of internationalization of modern sculpture.